2010
DOI: 10.1007/s00228-010-0863-9
|View full text |Cite
|
Sign up to set email alerts
|

VKORC1-1639G>A, CYP2C9, EPHX1691A>G genotype, body weight, and age are important predictors for warfarin maintenance doses in patients with mechanical heart valve prostheses in southwest China

Abstract: There were great interindividual differences in warfarin maintenance dosage (ranging from 0.6 to 8.4 mg/day) among the 127 patients with mechanical heart valve prostheses. VKORC1-1639G>A, CYP2C9, EPHX1691A>G polymorphism, body weight, and age were found to affect the dose demands. Multiple linear regression models incorporating genetic polymorphisms of VKORC1, CYP2C9, EPHX1691A>G, and the nongenetic factors of age and body weight were developed, and explained up to 76.8% of the total variation (adjusted R (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Our findings are in concordance with previous studies carried on a Japanese [14], Chinese [41] and Indonesian population [23]. This is in contrast to other reports [7][8][9].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our findings are in concordance with previous studies carried on a Japanese [14], Chinese [41] and Indonesian population [23]. This is in contrast to other reports [7][8][9].…”
Section: Discussionsupporting
confidence: 50%
“…The median (25th-75th percentiles) age of the 84 patients was 39 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) years. Forty-one were men and 43 were women.…”
Section: Demographic Data Of the 84 Studied Subjectsmentioning
confidence: 99%
“…The lower warfarin dose in Asians suggests that future studies on additional defective CYP2C9 alleles in Asians or on other factors affecting the activity of CYP2C9 are needed. Recently Gu et al [42] reported that Chinese patients with the CYP2C9 IVS3-65 GC or CC genotype received lower doses of warfarin (0.9 Ϯ 0.2 mg day -1 ) than those with the CYP2C9*1/*1 genotype (2.6 Ϯ 1.4 mg day -1 ). Still, the plasma total and unbound warfarin concentrations were significantly lower in the patients with the CYP2C9*1/*1 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…A recent association study with a Chinese population also confirmed this observation [16]. Candidate gene studies have also detected associations between other SNPs and warfarin dose, such as SNPs in CYP2C19 (cytochrome P450, family 2, subfamily C, polypeptide 19) [17], GGCX (gamma-glutamyl carboxylase) [18], [19], [20], [21], EPHX1 (epoxide hydrolase 1) [21], [22], [23], [24], CALU (calumenin) [25], and MPZ (myelin protein zero) [12]. However, the associations of these SNPs with warfarin dose were inconsistent.…”
Section: Introductionmentioning
confidence: 66%
“…Three variants, rs1057910 (*3), rs4917639, and rs9332127 in the CYP2C9 gene have been reported to be associated with warfarin dose [12], [22], [24]. Among these variants, rs9332127 was not detected in Caucasian individuals but was reported to affect warfarin dose in Chinese people [22], [24], [35]; however, no significant association was observed in Indonesian populations [36]. In our study and previous studies [12], [37], univariate analyses showed that rs4917639 was significantly associated with warfarin dose.…”
Section: Discussionmentioning
confidence: 99%